Influence of surface treatments on corrosion resistance properties of ultrafine grained titanium alloys for biomedical applications - Pérez, Diego (Universidade Federal de São Carlos, 2019)
Titanium and its alloys are used as biomaterials because their excellent combination of high corrosion resistance, low modulus of elasticity and biocompatibility. However, titanium and its alloys cannot meet all the clinical requirements. In this sense, in order to improve the electrochemical and bioactive properties, this thesis aims to evaluate the effect of the severe plastic deformation as well as the surface modification treatments on the corrosion resistance and bioactivity of titanium alloys (α' + β) and (β). The titanium alloys, Ti13Nb13Zr (α' + β) and Ti35Nb7Zr5Ta (β), were deformed by the high-pressure torsion (HPT) method. Afterward, surface modification treatments, such as the anodization and chemical treatments, were carried out both in samples non-deformed and deformed by HPT. Finally, corrosion and bioactivity tests were performed in simulated body fluid (SBF). The tests were performed on samples with treated surfaces compared with non-treated surfaces in the deformed and undeformed conditions. The samples’ microstructures were analyzed by confocal laser microscopy (CLM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). Hardness tests were also performed after the HPT process. On the other hand, surface modification treatments, and the formation of apatite in bioactivity assays were evaluated by scanning electron microscopy (SEM), with chemical analyzes carried out by dispersive energy spectroscopy (EDS) and phase identification by X-ray diffraction (XRD). In general, the corrosion resistance of the titanium alloys improved with the anodization treatment. Apatite deposits were observed on Ti13Nb13Zr alloy samples, in the conditions non-deformed and deformed by HPT. The Ti35Nb7Zr5Ta appears to have a lower apatite-formation ability compared to Ti13Nb13Zr.

Le titane et ses alliages sont utilisés comme biomatériaux en raison de leur excellente combinaison de résistance élevée à la corrosion, de faibles modules d'élasticité et de biocompatibilité. Cependant, le titane et ses alliages ne peuvent pas répondre à toutes les exigences cliniques. En ce sens, afin d’améliorer les propriétés électrochimiques et bioactives, cette thèse vise à évaluer l’effet de la déformation plastique sévère ainsi que des traitements de modification de surface sur la résistance à la corrosion et la bioactivité des alliages de titane (α '+ β) et (β). Les alliages Ti13Nb13Zr (α' + β) et Ti35Nb7Zr5Ta (β) ont été déformés par la méthode de torsion à haute pression (HPT-High Pressure torsion). Ensuite, des traitements de modification de surface, tels que l’anodisation et les traitements chimiques, ont été effectués dans des échantillons non déformés et déformés par HPT. Enfin, des tests de corrosion et de bioactivité ont été réalisés dans un fluide corporel simulé (SBF). Les tests ont été effectués sur des échantillons de surfaces traitées par rapport à des surfaces non traitées de conditions déformées et non déformées. La microstructure des échantillons a été analysée par microscope confocal à balayage laser (CLM), microscopie électronique à balayage (SEM) et diffraction des rayons X (XRD). Des tests de dureté sont également effectués après le processus HPT. D'autre part, les traitements de modification de surface et la formation d'apatite dans les tests de bioactivité sont évalués par SEM, analyses chimiques par spectroscopie d'énergie dispersive (EDS) et DRX. En général, la résistance à la corrosion des alliages de titane évaluées, améliorée avec le traitement d'anodisation. Des dépôts d'apatite ont été observés sur des échantillons d'alliage Ti13Nb13Zr, non déformés et déformés par HPT, pour les traitements de modification de surface proposés. Le Ti35Nb7Zr5Ta semble avoir une capacité de formation d'apatite inférieure à celle du Ti13Nb13Zr.
Influência dos tratamentos de superfície nas propriedades de resistência à corrosão de ligas de titânio de grão ultrafino para aplicações biomédicas
Influence de traitements de surface sur les propriétés de résistance à la corrosion d'alliages de titane à grains ultrafins pour des applications biomédicales
Keywords: Liga de titânio; Liga Ti13Nb13Zr; Liga Ti35Nb7Zr5Ta; Deformação plástica severa; Nanotubos de TiO2; Apatita; Resistência à corrosão; Bioatividade; Titanium alloys; Ti13Nb13Zr alloy; Ti35Nb7Zr5Ta alloy; Severe plastic deformation; TiO2 nanotubes; Apatite; Corrosion resistance; Bioactivity; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA